2021
DOI: 10.1007/s10620-021-07118-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease Pandemic on Health-Related Quality of Life of Patients with Inflammatory Bowel Disease

Abstract: Background To learn from the crisis caused by the coronavirus disease (COVID-19) pandemic and be prepared for future pandemics, it is important to investigate the impact of this period on the wellbeing of patients with inflammatory bowel disease (IBD). Aims To describe the health-related quality of life (HRQoL) and disease control of IBD patients during the first wave of the COVID-19 pandemic in The Netherlands. Methods Between March 17 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…To our knowledge, the only longitudinal study conducted during the COVID-19 pandemic reported that IBD-related HRQOL remained mostly stable during different phases of restrictions [3]. The result that COVID-19 played a negligible role in IBD-related HRQOL could be explained by the evidence that social distancing and staying at home are already an everyday problem for IBD patients because of speci c symptomatology (e.g., uncontrolled bowel movements, pain, and fatigue) [3,5]. Furthermore, it is possible that being in isolation due to the restrictions could even decrease the discomfort caused by the management of the disease and the fear of contracting COVID-19 in these patients [4].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…To our knowledge, the only longitudinal study conducted during the COVID-19 pandemic reported that IBD-related HRQOL remained mostly stable during different phases of restrictions [3]. The result that COVID-19 played a negligible role in IBD-related HRQOL could be explained by the evidence that social distancing and staying at home are already an everyday problem for IBD patients because of speci c symptomatology (e.g., uncontrolled bowel movements, pain, and fatigue) [3,5]. Furthermore, it is possible that being in isolation due to the restrictions could even decrease the discomfort caused by the management of the disease and the fear of contracting COVID-19 in these patients [4].…”
Section: Discussionmentioning
confidence: 92%
“…These ndings con rm the results of our preliminary cross-sectional study [4] in which the COVID-19-related psychological distress played unexpectedly only a negligible role on IBD-speci c HRQOL. To our knowledge, the only longitudinal study conducted during the COVID-19 pandemic reported that IBD-related HRQOL remained mostly stable during different phases of restrictions [3]. The result that COVID-19 played a negligible role in IBD-related HRQOL could be explained by the evidence that social distancing and staying at home are already an everyday problem for IBD patients because of speci c symptomatology (e.g., uncontrolled bowel movements, pain, and fatigue) [3,5].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar results have been noted among IBD patients. Although some studies indicate lower quality of life as an effect of the pandemic, other investigators support that despite recent barriers in IBD patients' healthcare, such as delays in procedures, appointments, and drug inaccessibility, the quality of life has not changed significantly [21][22][23][24]. For example, in the Netherlands, investigators reported worsening in quality of life and gastrointestinal symptomatology, but a tertiary care center in Saudi Arabia did not reveal worsening in IBD patients' quality of life [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Results from empirical studies are, however, controversial. Some investigations found that, during the stay-at-home period, up to one third of IBD patients reported poor HRQoL and moderate to severe anxiety and depressive symptoms [39][40][41][42][43] whereas, in contrast, other investigations showed that disability and HRQoL were unaffected by the COVID-19 pandemic [44][45][46]. The conclusions of those previous studies are, however, limited by the lack of a control for DA.…”
Section: Introductionmentioning
confidence: 96%